Long QT syndrome induced by elevated dose of Fluoxetine Cloridrate: case report - da Nóbrega Borges, José Victor; Ferraz, Marta Junqueira Reis; Januzzi, Werlley de Almeida; Leila, Samira Abdel Correia; Gomes Souto, José; Ejima, Gustavo Werneck (Brazilian Journal of Case Reports, 2024)
Introduction: Long QT syndrome is a clinical condition that affects cardiac repolarization with an increased risk for the development of severe ventricular arrhythmias. The acquired form can be induced by drugs, such as selective serotonin reuptake inhibitors. Case report: E.A.C.G., female, 83 years-old, previously diagnosed with major depressive disorder in use of Fluoxetine the 80mg/day, was admitted in the emergency department after a syncopal event. An important widening of the QT interval was noted on the occasion, with a corrected value of 580ms. A 24-hour Holter monitoring showed increased ectopic ventricular activity (18% of beats), prolonged QT interval (up to 630 ms), and high-complexity ectopic ventricular beats. Non-sustained ventricular tachycardia was also observed (1030 episodes). The prolonged QT interval was associated to an elevated dose of Fluoxetine. Discussion: We believe that the coexistence between a high dose of Fluoxetine and other risk factor such as female sex and increased age contributed to the development of the case presentation. Conclusion: The rising prevalence of depression in the geriatric population and the indiscriminate use of antidepressive agents such as selective serotonin reuptake inhibitors may contribute to an increase in potentially severe cardiovascular complications.